The Dilemmas of Scientific Research Cooperation and Their Resolution From the Perspective of Evolutionary Psychology - Wang, Gaofeng; Kong, Qingqing (Frontiers in Psychology, 2019)
Scientific research cooperation has become a mainstream trend of social development. It can promote resource sharing, help group members complement each other’s advantages, and improve scientific research efficiency. With the deepening of scientific research cooperation, there have also been problems such as the uneven strength of partners, gender discrimination, and group exclusionary behavior. People often explore the causes of these problems in terms of the process of scientific research cooperation, but doing so fails to solve the substantive problems effectively. We thus seek to trace the psychology of people participating in scientific research cooperation from the perspective of evolutionary psychology so as to analyze the root causes of scientific research cooperation problems. This paper first discusses the importance of scientific research cooperation, then enumerates common problems in scientific research cooperation, analyzes them from the perspective of evolutionary psychology, and proposes solutions to these problems from the perspective of regulating people’s psychology. This article illustrates how the many perspectives and theories of evolutionary psychology can solve problems in other disciplines and fields, and indeed that all human social activities can be explained by evolutionary psychology, which opens up a broader field of research for evolutionary psychology.